Constructing potassium and hydroxyl co-doped dual-dipole structures on highly active 3D g-C3N4 surfaces for highly boosting photocatalytic hydrogen peroxide production efficiency in pure water - Jiaxing Wu; Jiajie Yu; Fan Fan; Runhua Li; Mengxiang Wang; Gang Li; Yuting Wang; Yongpeng Cui; Daoqing Liu; Yajun Wang; Wenqing Yao (Green Chemical Engineering)
Producing hydrogen peroxide (H2O2) through visible-light-driven photocatalytic oxygen reduction in pure water is crucial for sustainable ecological applications but poses significant challenges. It include the rapid recombination of electron-hole pairs and a scarcity of effective catalytic sites, which traditionally limit the process efficiency. To address these issues, we have developed a novel catalyst, designated as KCNOH, which consists of a three-dimensional (3D) porous g-C3N4 framework doped with potassium (K+) and modified with surface hydroxyl groups (–OH). This design significantly enhances H2O2 yield, achieving 91.36 μmol g−1 h−1 (cut 420 nm)—a yield approximately 36 times higher than conventional bulk g-C3N4 (2.57 μmol g−1 h−1). The introduction of a 3D porous structure provides an abundance of active-sites. The dual-dipole mechanism, facilitated by K+ ions and hydroxyl groups, plays a pivotal role by efficiently transporting photogenerated electrons and consuming holes, respectively. Through density functional theory (DFT) calculations, the changes in the band structure of the catalyst caused by the doping of K+ and the grafting of –OH were elucidated. In addition, the transition state affinity of oxygen induced by the –OH was also studied to reveal the synergistic catalytic mechanism. This mechanism markedly reduces carrier recombination and accelerates charge migration, underscoring its importance in catalyst design. Our findings not only improve the understanding of charge dynamics but also open novel perspectives for the design of highly-efficient composite materials, which is crucial for energy and environmental applications.